Virtual reality (VR) in breast cancer awareness (BCA) program - Sowtali, Siti Noorkhairina (2023)
1. Evidence from literatures on breast cancer along with project leader and her FYP students’ research findings. 2. Previous BCA program organized by the team. 3. Hands on: Breast self-examination (BSE)